People, People S Emergency and Democracy: Disputed Categories - Friz-Echeverria, C (UNIV VALENCIA, DEPT PREHISTORIA & ARQUEOLOGIA, 2024)
This article offers a reflection on the political scope of the "social outbreaks", based on the possible relationships that can be established between "social outbreaks", understood as processes of popular emergency, "people" and "democracy". Can social outbreaks be considered processes of popular emergency? If so, can they be thought as processes of democratic deepening, understanding democracy as a regime of people sovereignty? The proposed reflection has as reference and motivation the cycle of mobilizations of Chile October 2019. For this reason, it mainly reviews texts about this process, which are complemented with sources that allow a more adequate focus on the links between people, emergency and democracy. The essay purpose is to show that the political scopes of emergency processes constitute a disputed issue, subject to conflict of interpretations. An attempt is made to show this struggle based on the controversial nature of the concepts "people", "emergency" and "democracy", and the links that can be established between them.